2020
DOI: 10.1002/chir.23241
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical chiral chromatographic technique and docking studies for enantioselective separation of meclizine hydrochloride: Application to pharmacokinetic study in rabbits

Abstract: Enantiomeric resolution and molecular docking studies of meclizine hydrochloride on polysaccharide‐based chiral stationary phase comprising cellulose tris(4‐methylbenzoate) chiral selector (150 × 4.6 mm, 3.0 μm) were presented. The mobile phase used was acetonitrile:10mM ammonium bicarbonate (95:05, v/v). The developed technique was used to perform the enantioselective assay of meclizine hydrochloride in its marketed formulation. The elution order of meclizine hydrochloride enantiomers was determined by dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A pair of antihistamine enantiomers could have different biological activities and pharmacological profiles. For example, the disparate pharmacokinetic properties of meclizine enantiomers have been demonstrated that the drug concentration of R ‐meclizine was found to be higher than S ‐meclizine in the rabbits, and significant variation in the stereo‐specific disposition of the meclizine enantiomers is marked with an obvious difference in most of the pharmacokinetic parameters between the two enantiomers [9]. Orphenadrine was proven to show stereoselectivity in binding to the human serum albumin [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A pair of antihistamine enantiomers could have different biological activities and pharmacological profiles. For example, the disparate pharmacokinetic properties of meclizine enantiomers have been demonstrated that the drug concentration of R ‐meclizine was found to be higher than S ‐meclizine in the rabbits, and significant variation in the stereo‐specific disposition of the meclizine enantiomers is marked with an obvious difference in most of the pharmacokinetic parameters between the two enantiomers [9]. Orphenadrine was proven to show stereoselectivity in binding to the human serum albumin [10,11].…”
Section: Introductionmentioning
confidence: 99%